Factors Influencing Consumer Purchase Intention of "KU Phuphan Black-Bone Chicken Product" in Sakon Nakhon Province, Thailand : A Study Based on the Theory of Planned Behavior (TPB) (International Journal of Management and Sustainability, 2017)
The purpose of this research was to study the factors influencing Thai consumers’ purchase intentions of KU Phuphan Black-bone Chicken product in Sakon Nakhon Province by using the Theory of Planned Behavior (TPB). KU Phuphan black-bone chicken is the rare chicken breed which is completely black inside and out despite its white feathers, developed by Thai researchers in Sakon Nakhon province and now was widely known as the economic animal. It was discovered that many previous studies conducted to focus on the genetics and nutrition; however, there was a lack of research concerning the marketing and consumer aspects. The quantitative research approach was adopted in this study. The research data was gathered using a questionnaire designed from the Theory of Planned Behavior (TPB). Using a total sample of 400 respondents who have recognized KU Phuphan Black-bone chicken product, a survey was developed and conducted in Sakon Nakhon province, Thailand. The results revealed that all three factors influenced consumers’ purchase intention. Attitude toward behavior and subjective norm had positively influenced on purchase intention. Consumers who had higher purchase intention of KU Phuphan Black-bone chicken product had significant higher attitudes about buying the product. In addition, an influence of subjective norm factor like parents, peers and media also played an important role in considering purchasing the product. Meanwhile, perceived behavior control factor such as availability of product and place to buy least influenced on purchase intention. Findings provided by this study will be helpful for marketers of KU Phuphan Black-bone Chicken product and others relevant to this business for planning, adapting and improving theirs related marketing activities.